Organizational crime: causes, explanations and prevention in a comparative perspective - Pohlmann, Markus; Dannecker, Gerhard; Dölling, Dieter; Hermann, Dieter; Höly, Kristina; Trombini, Maria Eugenia; Mitra, Subrata Kumar (Organization, management and crime - Organisation, Management und Kriminalität, 2023)
How to Explain and Fight Organizational Crime -- How to Analyze Organizational Crime -- The Development of the German Criminal Regulations against Corruption in the Public Sector -- The Development of German Criminal Law against Corruption in the Private Sector -- German Corruption Cases Reflected in Criminal Files -- Compliance, Integrity, and Prevention in the Corporate Sector -- Limits of Formal Regulation -- Experimental Corruption Research in Germany -- The German Organ Transplant Scandal -- Decision-making Processes of Physicians after the Organ Donation Scandal in Germany -- In Search of Organizational Crime in the U.S -- Formal Rules and Institutional Increments in Brazil -- Organizational Crime in Brazil -- The Anti-corruption Mindset of Brazilian Law Enforcers -- New Laws and Law Enforcement to Fight against Bribery in China -- Detected Cases of Bribery in China -- Companies as Responsible Actors and Corporate Citizens -- The Puzzling Resilience of Organizational Wrongdoing.